Sinkretisme Agama Dan Budaya Pada Bingkai Tradisi Lokal Gebyak Dusun di Dusun Pacet Made, Mojokerto, Jawa Timur - Yunasta Sarifa; Wahid Nur Tualeka; Mahmud Muhsinin (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
Research on religious and cultural syncretism in the frame of the local gebyak halmet tradition in Pacet Made hamlet, Mojokerto, East Java aims to find out the history of gebyak halmet, its process, and religious and cultural syncretism in the frame of the local gebyak halmet tradition, as well as the responses of the community and related religious leadees gebyak Dusun local tradition. This study uses qualitative research methodes to obtain descriptive data in the form of words in spoken and written form. And using an ethnographic approach, namely research studies on society and culture. Data collection techniques in this study used observation, documentation and interviews. The result and discussion of this study is the discovery of syncretism in the local tradition of gebyak in Pacet Made hamlet, namely the history of this tradition which wa originally to reject reinformecent due to the occurrence of illness and trance in Pacet Made hamlet, now it has developed into a form of gratitude to God. And what was originally this tradition only gave offerings to pepunden, now it is experiencing a fusion of religion and culture, namely in the procession of the gebyak hamlet tradition there are tahlilan and join prayer.